2007
DOI: 10.1002/bjs.5725
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological study of the relationship between volume and outcome after abdominal aortic aneurysm surgery in the UK from 2000 to 2005

Abstract: Increased annual volumes were associated with significant reductions in mortality for elective and urgent AAA repair, but not for repair of ruptured AAAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
112
1
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 122 publications
(123 citation statements)
references
References 45 publications
7
112
1
3
Order By: Relevance
“…Historically, many district general (local) hospitals in the UK undertook emergency AAA surgery, but health regions in the UK now centralise vascular resources at a single tertiary hospital, because outcome for aortic surgery is better in high-volume compared with low-volume vascular centres [17]. Concomitant increases in the transfer time to hospital faced by patients with ruptured AAA do not appear to affect mortality adversely.…”
Section: Emergency Abdominal Aortic Aneurysm Repairmentioning
confidence: 99%
“…Historically, many district general (local) hospitals in the UK undertook emergency AAA surgery, but health regions in the UK now centralise vascular resources at a single tertiary hospital, because outcome for aortic surgery is better in high-volume compared with low-volume vascular centres [17]. Concomitant increases in the transfer time to hospital faced by patients with ruptured AAA do not appear to affect mortality adversely.…”
Section: Emergency Abdominal Aortic Aneurysm Repairmentioning
confidence: 99%
“…one is to bisect the material at the median and compareo utcome between the two groups (8,16). Another is to divide the material in similar sized groups, quartiles or quintiles (6, 10,12,16,17). Several studies use arbitrary divisions or expert opinion (2, 4, 5, 9, 11).…”
Section: Resultsmentioning
confidence: 99%
“…The average mortality of 7.7% was reached in centres performing only 14 elective repairs per year or more. Holt (16) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aliteratures earch of 20973 rAAAs by Laukontaus (3) disclosed that 12 studies had excluded patients unfit for surgery from analysis and that 14 studies considered one fourth of the patients moribund (weighted mean 24%, range 7-54%). Indeed, alarge epidemiological study on AAA surgery in the UK from 2000 to 2005 revealed that 7927 of 14389 rAAA werenot operated on, yielding atotal hospital mortality of 64.5% (4).…”
mentioning
confidence: 99%